Efficacy, effectiveness and safety of fumaric acid esters in the treatment of psoriasis: a systematic review of randomized and observational studies. (19th July 2016) - Balak, D.M.W.; Fallah Arani, S.; Hajdarbegovic, E.; Hagemans, C.A.F.; Bramer, W.M.; Thio, H.B.; Neumann, H.A.M.
Summary: Fumaric acid esters (FAEs) are increasingly used as a systemic treatment for psoriasis, but there are still uncertainties regarding their suitability. The objective of this systematic review was to assess the evidence for the efficacy and safety of FAEs in psoriasis treatment. A systematic literature search was performed in seven databases up to 17 August 2015. Inclusion criteria were studies that reported clinical effects of FAEs in patients with psoriasis without restrictions in study design, language or publication date. Methodological quality of randomized controlled trials (RCTs) and overall level of quality were assessed using the Cochrane risk of bias tool and the Grading of Recommendation, Assessment, Development and Evaluation approach, respectively. A total of 68 articles were included. There were seven RCTs (total 449 patients) that had an unclear risk of bias and were too clinically heterogeneous to allow a meta‐analysis. Overall, mean Psoriasis Area and Severity Index decreased by 42–65% following 12–16 weeks of treatment. There were 37 observational studies (a total of 3457 patients) that supported the RCT findings, but most were uncontrolled with a high risk of bias. Commonly reported adverse events included gastrointestinal complaints and flushing, leading to treatment withdrawal in 6–40% of patients. Several case‐reports described rare adverse events, such as renal Fanconi syndrome and progressive multifocal leukoencephalopathy. There was a lack of studies focusing on long‐term use and comparisons with other treatments. This review concluded that there is low‐quality evidence to recommend the use of oral FAEs to treat plaque psoriasis in adult patients. Studies focusing on long‐term safety and comparison with systemic psoriasis treatments could lead to a better understanding of the role of FAEs as a treatment for psoriasis. Abstract : What's already known about this topic? The introduction of fumaric acid esters (FAEs) for the treatment of psoriasis has not been based on high‐quality evidence stemming from well‐performed randomized controlled trials. FAEs are licensed in Germany. Outside Germany, the use of FAEs to treat psoriasis has been limited and is unlicensed. What does this study add? This systemic review provides a comprehensive summary and appraisal of available studies that reported the clinical effects of FAEs in patients with psoriasis. There was low‐quality evidence to recommend the use of FAEs for the treatment of psoriasis with unclear and high‐risk studies reporting favourable efficacy and tolerability of FAEs. Studies on the long‐term use of FAEs and comparative studies were lacking.